Intelligent Orchestration Algorithm for Power Backbone Optical Network with Service QoS Awareness. Issue 1 (1st December 2022) - Liang, Wenjuan; Liang, Yutu; Zhu, Wenhong; Deng, Xiaozhi
Abstract: The power backbone optical network has the shortcomings of low spectrum utilization, and high service blocking rate, which cannot satisfy the differentiated quality of service (QoS) demands of the power services. This paper proposed a power backbone optical network architecture that uses elastic optical networks (EONs) to improve frequency utilization, and proposes an upper confidence bound (UCB)-based intelligent orchestration algorithm for power backbone optical network. Simulation verified that the proposed intelligent orchestration algorithm can improve the performance of the intelligent bandwidth allocation and meet the requirements of differentiated QoS demands.